2013
DOI: 10.1007/978-94-007-7832-0_15
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Imaging of Tissues: Techniques and Methods of Analysis

Abstract: In this chapter, we describe biomedical applications of infrared microscopic imaging applied to human tissue sections. the central focus is human diseases including cervical cancer, neurodegenerative pathologies, and dysfunctions of cardiac and liver tissues. In addition, we briefly describe the fundamentals of FtIR imaging instrumentation along with spectral pre-processing and hyperspectral image reconstruction. the chapter concludes with a summary of what is required to take FtIR imaging technology into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 142 publications
3
53
0
Order By: Relevance
“…The FTIR spectra of DMSP and its precursors, methionine and cysteine (Fig. B), and the published literature (Dovbeshko et al ., ; Movasaghi et al ., ; Malek et al ., ), support our deduction that these bands arise from thiol and/or amino groups. Closer examination of the chemical images showed that the band at 2675 cm −1 is confined to the accumulation body only (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The FTIR spectra of DMSP and its precursors, methionine and cysteine (Fig. B), and the published literature (Dovbeshko et al ., ; Movasaghi et al ., ; Malek et al ., ), support our deduction that these bands arise from thiol and/or amino groups. Closer examination of the chemical images showed that the band at 2675 cm −1 is confined to the accumulation body only (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Absorption bands corresponding to the aliphatic stretching vibrations (3015–2850 cm −1 ) and the ester C = O stretches (1748 cm −1 ) of lipids are prominent features of region 1, although less intense in comparison to regions 2 and 3. The intense bands at 1120 cm −1 and 1190 cm −1 were difficult to assign but most likely arise from the C–O, C–C and/or CO–O–C stretches of carbohydrates, nucleic acids, amino acids and proteins (Malek et al ., ). However, we cannot rule out the possibility that they may also arise from the stretching vibrations of PO 2− in phospholipids given the obvious bands associated with lipid.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The advances in FT-IR for tissue imaging have been driven in a large part by three key developments: 1) increased speed of data acquisition due to the availability of large Focal Plane Array (FPA) detectors which typically have thousands of IR sensitive detectors 1,2 , 2) development of advanced processing algorithms and computational power to handle large hyperspectral data sets 3 , and 3) modeling of FT-IR imaging systems to maximize spatial resolution 4,5 . There have been numerous high quality and very extensive articles reviewing the field of FT-IR spectroscopy recently [6][7][8][9][10][11][12][13][14][15][16] , in addition to a Nature Protocols paper that details the steps to obtain point spectra or maps from tissues 17 . In this paper, we will focus on the protocol to obtain images of tissues using a 128 x 128 FPA detector in a modified FT-IR system with high-definition capabilities.…”
Section: Introductionmentioning
confidence: 99%